Update on the Functionalization of Sentencing Guidelines in the Criminal Law System in Indonesia - Zahlan, Muhammad; Arief Fakrulloh, Zudan (Pelopor Publikasi Akademika, 2024)
Renewing the functionalization of sentencing guidelines in the criminal law system in Indonesia is the main topic of this article. The central purpose of this reform is to increase fairness, effectiveness, and efficiency in criminal law enforcement in Indonesia. With structured and clear sentencing guidelines, it is hoped that the sentencing process can be carried out consistently and transparently, providing fair decisions for all parties involved. This article highlights several important aspects that need to be considered in renewing the functionalization of criminal law in Indonesia. First, justice in the sentencing process must be maintained by ensuring equal treatment for all individuals before the law. Second, technological innovation is crucial for increasing efficiency and accuracy in the legal process. Third, crime prevention and rehabilitation are also important focuses for creating a safer and more civilized society. In addition, the significance of international cooperation is increasing the capacity of law enforcement officials, as well as transparency and accountability are also emphasized in this article. Challenges such as harmonization of regulations, limited resources, resistance from certain parties, and so on, must be overcome with strong commitment and cooperation from various related parties. It is hoped that with a deep understanding of these challenges, updating the functionalization of criminal law and sentencing guidelines in Indonesia can have a positive impact on efforts to achieve better legal justice. Cross-sector collaboration, innovation, and strong commitment from the government, legal authorities, and society as a whole are the main keys to realizing a fairer and more effective criminal legal system in the future.